Pendidikan Karakter dalam Keluarga Single Parent di Desa Talang Belido - Muhammad Rafii; Mastikawati Mastikawati; Dewi Tumatul Ainin; Nori Nopita Sari; Nazoma Nazoma; Zulkifli Zulkifli (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
Character education is so important with the consideration that the digital generation is increasingly displaying behavior in the real world and the virtual world unnaturally. It is worth exploring how a family educates children in their life or family environment. However, what is of concern in this article is character education in single parent families in Talang Belido Village. By utilizing primary and secondary data, obtained from observations and interviews as well as documentation, the researcher attempted to collect relevant data related to the topic of this research. Data were analyzed following data reduction techniques, data display, and data verification to draw conclusions. This article draws the conclusion that character education in single parent families gets great attention for the head of the family. Even though they realize they have no knowledge, experience and are able to give advice to their children. Character values that are often conveyed are honesty, religious and respect for others. However, it is also known that the obstacles experienced by single parent families are the influence of the children's playing or socializing environment, the educational background of the parents, and the availability of insufficient time to fully interact with their children